1989
DOI: 10.1073/pnas.86.15.5958
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the D21S55 region on chromosome 21 in the pathogenesis of Down syndrome.

Abstract: The duplication of a specific region of chromosome 21 could be respotisible for the main features of Down syndrome. To define and localize this region, we analyzed at the molecular level the DNA of two patients with partial duplication of chromosome 21. These patients belong to two groups of Down syndrome patients characterized by different partial trisomies 21: (i) duplication of the long arm, proximal to 21q22.2, and (ii) duplication of the end of the chromosome, distal to 21q22.2 We assessed the copy number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
112
0
3

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(119 citation statements)
references
References 31 publications
2
112
0
3
Order By: Relevance
“…In situ hybridization studies show that DYRK1A is highly expressed in brain gray matter, spinal cord, and retina in developing murine embryos (Song et al, 1996;Rahmani et al, 1998;Hämmerle et al, 2003a;Mao et al, 2003;Marti et al, 2003) and in the cerebral cortex, cerebellum, and pyramidal cell layer in the hippocampus in adult mice (Guimera et al, 1996). DYRK1A has been considered a good candidate gene for the Down syndrome phenotypic abnormalities (reviewed in Epstein, 2000;Vicari et al, 2000;Nadel, 2003) due to its localization in the Down syndrome critical region of chromosome 21 (Rahmani et al, 1989(Rahmani et al, , 1990Delabar et al, 1993;Shindoh et al, 1996;Song et al, 1996), its overexpression in the brain of Down syndrome patients (Guimera et al, 1999), and the neurobehavioral alterations shown by transgenic mice overexpressing the gene (Smith and Rubin, 1997;Altafaj et al, 2001). The recent observation that the size of dendrites in some brain areas is reduced in DYRK1A haploinsufficient mice indicates that DYRK1A dose reduction could affect the length and the complexity of the dendrites (Fotaki et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ hybridization studies show that DYRK1A is highly expressed in brain gray matter, spinal cord, and retina in developing murine embryos (Song et al, 1996;Rahmani et al, 1998;Hämmerle et al, 2003a;Mao et al, 2003;Marti et al, 2003) and in the cerebral cortex, cerebellum, and pyramidal cell layer in the hippocampus in adult mice (Guimera et al, 1996). DYRK1A has been considered a good candidate gene for the Down syndrome phenotypic abnormalities (reviewed in Epstein, 2000;Vicari et al, 2000;Nadel, 2003) due to its localization in the Down syndrome critical region of chromosome 21 (Rahmani et al, 1989(Rahmani et al, , 1990Delabar et al, 1993;Shindoh et al, 1996;Song et al, 1996), its overexpression in the brain of Down syndrome patients (Guimera et al, 1999), and the neurobehavioral alterations shown by transgenic mice overexpressing the gene (Smith and Rubin, 1997;Altafaj et al, 2001). The recent observation that the size of dendrites in some brain areas is reduced in DYRK1A haploinsufficient mice indicates that DYRK1A dose reduction could affect the length and the complexity of the dendrites (Fotaki et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The human Dyrk1A gene maps to the 21q22.2 region of chromosome 21, in the Down syndrome critical region (Rahmani et al, 1989(Rahmani et al, , 1990Delabar et al, 1993;Shindoh et al, 1996;Song et al, 1996), and transgenic mice harboring an extra copy of this gene exhibit cognitive deficits and motor abnormalities characteristic of Down syndrome (Smith and Rubin, 1997;Altafaj et al, 2001). The human and rodent Dyrk1A gene are ubiquitously expressed in adult and fetal tissues with high expression in the brain and the heart during development (Guimera et al, 1996(Guimera et al, , 1999Song et al, 1996;Rahmani et al, 1998;Hämmerle et al, 2003a;Mao et al, 2003;Marti et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The earliest studies hypothesized that a relatively small region of HSA21 may play a major role in DS phenotypes, and proposed the concept of a DS critical region (DSCR). 4,7,18,19 The DSCR was defined with a proximal boundary between markers D21S17 (35 892 kb) and D21S55 (38 012 kb), and a distal boundary at MX1 (41 720 kb). 5,8 This is a region spanning 3.8 -6.5 Mb and containing B25 -50 genes.…”
Section: Introductionmentioning
confidence: 99%
“…The successful application of direct cDNA selection for identifying genes from chromosome 21 has recently been reported (11)(12)(13). We have utilized exon amplification to isolate over 100 gene fragments from a 2.5 Mb region of chromosome 21 between loci CBR and ERG, which is present in three copies in common in many DS individuals with partial trisomy 21 (4,5,7,10). Localization of these gene fragments to a physical map of the region has imparted higher resolution to the physical map and contributes to integration with a transcript map.…”
Section: Introductionmentioning
confidence: 99%
“…Since the association of Down syndrome (DS) with trisomy for human chromosome 21 (1,2), the study of this common birth defect has progressed from cytogenetic analyses of patient chromosomes (3) through the molecular characterization of gene and sequence dosage in individuals with partial trisomy 21 (4)(5)(6)(7)(8)(9). The resulting genotype-phenotype correlations that have emerged define subregions of the chromosome that likely contain genes contributing to specific features of DS (5,10).…”
Section: Introductionmentioning
confidence: 99%